IFCS-2006 Lublana - kilka refleksji - Sokołowski, Andrzej; Jajuga, Krzysztof; Gatnar, Eugeniusz (IFCS-2006 Lublana - Some Remarks, 2007)
In the paper we present some facts abort International Federation of Classification Societies and the remarks on the papers presented in IFCS conference which took place in Lublana.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 39-45